Medicinal potential of 3,4,5-Trihydroxy-N-O-[(2 Methyl-1H-INdoL-3-YL)-Methylidene] benzohydrazide / Faezeh Tayeby - Faezeh , Tayeby (2017)
Background: In the new drugs design, investigation of hybrid molecules that might possess a synergistic result that leads to a greater activity than each of its constituents may provide a compound with more enhanced pharmacological properties. Aim: Subsequently a newly synthesized 3,4,5-trihydroxy-N'-[(2-methyl-1H-indol-3-yl)-methylidene]benzohydrazide (TIBH) was tested for wound healing, ulcer prevention antioxidant, cytotoxicity and anti-microbial activities. Materials and methods: 1, 1- diphenyl-2-picryl hydrazyl (DPPH) and Ferric-reducing antioxidant power (FRAP) assays were used to test TIBH antioxidant activity. 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay was carried out to measure the TIBH cytotoxicity against human normal fibroblast. Minimal inhibitory concentration (MIC) method was performed to test TIBH antimicrobial effect against two standard strains of Staphylococcus aureus and Escherichia coli which are known pathogens to cause wound infections. Gastro-protective and wound healing activity of TIBH were studied in vivo. Results: TIBH showed a remarkable DPPH radical scavenging activity, with IC50 values of 33.8 μg/ml and a very strong FRAP value when compared to reference controls. Cytotoxicity result showed TIBH in concentration more than 154 μM (50 μg/ml) was toxic against human normal fibroblast. Antimicrobial assay showed TIBH MIC against two tested strains was recorded greater than the highest tested concentration of the TIBH (200 μg/ml). Evaluation of the effect of TIBH in wound healing showed that TIBH 10 mg/kg increased wound closure, promoted faster reepithelization and more collagen synthesis, decreased number of inflammatory cells, decreased Bax protein expression and finally increased SOD activity and decreased lipid peroxidation. In ulcer prevention study TIBH increased mucus secretion, decreased gastric acidity, up-regulation of HSP70 protein, down-regulation of Bax protein, decrease of the lipid peroxidation and the increase of the SOD activity in gastric tissue. Acute toxicity assay exposed valuable information on the safety of this compound. Conclusion: In conclusion TIBH showed to be a strong antioxidant, a wound healing and ulcer preventer promoter.